The positive psychology of challenge: Towards interdisciplinary studies of activities and processes involving challenges - Horikoshi, Keisuke (Frontiers in Psychology, 2023)
Activities and processes involving challenges are a natural part of life for most people and are highlighted in times of rapid change and global issues. This article argues that more studies around activities and processes involving challenges should be conducted with a focus on the concept of challenge in the context of well-being and optimal functioning. The concept of challenge is important because it is explicitly embedded in many major themes of positive psychology and can be a key concept in creating perspectives and frameworks to connect and integrate multiple elements in positive psychology to promote advancements in the field. Studying activities and processes involving challenges is also important from the perspective of dialectically integrating the positive and negative elements encompassed in the concept of challenge. The article also proposes to label activities and processes involving challenges as “challengership” and that an interdisciplinary area to study “challengership” (named “challengership studies”) should be created, which can collaborate with positive psychology for mutual development. The positive psychology of challenge/challengership is likely to provide opportunities for further advancement of positive psychology by creating more integrated knowledge of how to flourish when faced with challenges individually and collectively. The knowledge created in these areas can also be applied to education, coaching, and training at schools and organizations to meet the needs of the times, where skills of challengership should be considered trainable.